Achieving market dominance through radical change - Vollmann, Thomas E. (Boston, Mass. : Harvard Business School, 1996)
The Transformation Imperative shows why change initiatives like reengineering, continuous improvement, and employee empowerment, when implemented by themselves, are not enough to achieve dominance in today's rapidly evolving business environment. Only when change programs are deep and fully integrated across the organization can an enterprise truly be transformed. And the alternative to transformation, says the author, is certain destruction.
Drawing on the research efforts of Manufacturing 2000, a collaborative project between leading multinational companies and the International Institute for Management Development (IMD) in Switzerland, The Transformation Imperative presents useful tools and a practical framework for analyzing, implementing, and measuring change programs as well as for linking big-picture strategy with the nuts-and-bolts of change management.
Includes bibliographical references p. 257-260 and index.
Keywords: Organizational change -- Management; Organizational learning